Halotolerant bacteria with lipolytic activity isolated from Pilluana Salterns - San Martin - Flores-Fernández, Mónica L. (2010)
In order to isolate halotolerant bacteria with lipolytic activity from the Pilluana Salterns in San Martin, saline soil samples were collected and cultured in 5% salt water agar containing 0,5% yeast extract. It was pre-selected 55 bacteria with different morphological characteristics, these bacteria were grown simultaneously in 5% salt water agar containing 1% tributyrin, Tween 80 and olive oil. It was selected 14 bacteria based on the ability to hydrolyze specific substrates and shown high salt tolerance rate between 0 to 25%. These bacteria grew optimally at pH 7 and 37 °C, six were Gram positive and Gram negative eight, 12 bacteria hydrolyzed tributyrin, Tween 80 and olive oil, six produced amylases and proteases. The 14 halotolerant bacteria with lipolytic activity isolated from the Pilluana salterns are promising lipase production sources and oily waste bio-treatment.